2022
DOI: 10.1136/bmjopen-2021-058187
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with preoperative anxiety among patients undergoing surgery in low-income and middle-income countries: a systematic review and meta-analysis

Abstract: ObjectivesThis review aimed to determine the pooled prevalence of preoperative anxiety and its associated factors among patients undergoing surgery in low/middle-income countries (LMICs).MethodsWe searched PubMed, SCOPUS, CINAHL, Embase and PsychINFO to identify peer-reviewed studies on the prevalence and factors associated with preoperative anxiety among patients undergoing surgery using predefined eligibility criteria. Studies were pooled to estimate the prevalence of preoperative anxiety using a random-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…The prevalence of anxiety in our study is in accordance with previous assessments using alternative questionnaires such as APAIS 15,16 , APAIS-A-T 4 or STAI-scores 17,18 . Still, many systematic reviews and meta-analysis do not differentiate surgical-related from directly anaesthesia-related anxiety, resulting in a far range of 20-80% in reported prevalence of perioperative anxiety in current literature 19,20 . Recent evidence supports our claim of separating these two types of anxiety, as anxiety related to surgery remains higher compared to directly anaesthesia-related anxiety 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anxiety in our study is in accordance with previous assessments using alternative questionnaires such as APAIS 15,16 , APAIS-A-T 4 or STAI-scores 17,18 . Still, many systematic reviews and meta-analysis do not differentiate surgical-related from directly anaesthesia-related anxiety, resulting in a far range of 20-80% in reported prevalence of perioperative anxiety in current literature 19,20 . Recent evidence supports our claim of separating these two types of anxiety, as anxiety related to surgery remains higher compared to directly anaesthesia-related anxiety 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite various perioperative interventions, some patients proceed with surgery because of signi cant anxiety. However, no research has been done on the characteristics of patients who are anxious due to a non-response to perioperative interventions [8,9,10]. By analyzing the characteristics of patients who do not respond to interventions such as preoperative rehabilitation or education, it may be possible to select patients who require a higher level of intervention, such as consulting a psychiatrist or taking anti-anxiety medications [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…a surgical procedure), it is important to distinguish this type of anxiety with trait anxiety, which can be defined as an anxious personality [14]. It is reported that 48 to 56% of patients admitted for surgery experience preoperative anxiety, and even reaches 85% in day surgery patients, which may cause hemodynamic change during anesthetic induction as well as increase the requirement of anesthetics introperatively, leading to an increased risk of postoperative complications [15][16][17][18][19][20][21]. Given the high prevalence of preoperative anxiety, abundant protocols to reduce anxiety have been administrated before surgery including pharmacological therapy and non-pharmacological therapy.…”
Section: Introductionmentioning
confidence: 99%